2014
DOI: 10.1371/journal.pone.0094460
|View full text |Cite
|
Sign up to set email alerts
|

Prominent Steatosis with Hypermetabolism of the Cell Line Permissive for Years of Infection with Hepatitis C Virus

Abstract: Most of experiments for HCV infection have been done using lytic infection systems, in which HCV-infected cells inevitably die. Here, to elucidate metabolic alteration in HCV-infected cells in a more stable condition, we established an HCV-persistently-infected cell line, designated as HPI cells. This cell line has displayed prominent steatosis and supported HCV infection for more than 2 years, which is the longest ever reported. It enabled us to analyze metabolism in the HCV-infected cells integrally combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 54 publications
2
41
0
Order By: Relevance
“…The fact that HCV may interact with the cholesterol synthesis pathway has been suggested previously. HMGCoA reductase, a key enzyme of the cholesterol biosynthesis pathway, was shown to be elevated in HCV patients [39] and cholesterol levels are increased in Huh-7 cells infected with HCV [40,41]. In addition, our observation that statins, well known inhibitors of HMGCoA reductase, impede the increase of LD size caused by HCV 3a core protein, points out the crucial role that CE could play in HCV-induced steatosis as well as in HCV life cycle.…”
Section: Discussionmentioning
confidence: 80%
“…The fact that HCV may interact with the cholesterol synthesis pathway has been suggested previously. HMGCoA reductase, a key enzyme of the cholesterol biosynthesis pathway, was shown to be elevated in HCV patients [39] and cholesterol levels are increased in Huh-7 cells infected with HCV [40,41]. In addition, our observation that statins, well known inhibitors of HMGCoA reductase, impede the increase of LD size caused by HCV 3a core protein, points out the crucial role that CE could play in HCV-induced steatosis as well as in HCV life cycle.…”
Section: Discussionmentioning
confidence: 80%
“…It is known that GSH de novo synthesis is driven by Nrf2 (nuclear factor erythroid 2-related factor), one of the major cellular defense mechanisms against oxidative stress and a master regulator of different cytoprotective genes including those involved in the antioxidant GSH pathway [61]. It has been recently demonstrated that higher expression of nuclear Nrf2 contributes to persistent HCV infection and that knockdown of Nrf2 suppresses its persistent infection [62]. The authors suggest that the nuclear translocation of p-Nrf2 might play an important role in the expression of the genes which contribute to regulate apoptosis and HCV persistence [25,26,30,62].…”
mentioning
confidence: 99%
“…It has been recently demonstrated that higher expression of nuclear Nrf2 contributes to persistent HCV infection and that knockdown of Nrf2 suppresses its persistent infection [62]. The authors suggest that the nuclear translocation of p-Nrf2 might play an important role in the expression of the genes which contribute to regulate apoptosis and HCV persistence [25,26,30,62]. Accordingly, we found higher mRNA levels of GCL and GS enzymes during the recovery period; at the same time, Nrf2 protein content was highly expressed during the chronic phase.…”
mentioning
confidence: 99%
“…During gluconeogenesis and ketogenesis, NH 3 obtained from the deamination of amino acids is used to generate carbamoyl phosphate, and this product can be decomposed into citrulline and pyrimidine. Certain amino acids involved in the urea cycle, such as proline, ornithine arginine and citrulline, have been confirmed to participate in the TCA cycle by affecting the formation of fumarate [29,41]. Pyrimidine is used to synthesize uridine, which can be phosphorylated to produce uridine triphosphate.…”
Section: Discussionmentioning
confidence: 99%